The Epoxy-based composites with Size-Fractionated Waste Areca Sheath: An Experimental Investigation on the Macroscopic and Vibrational Properties (Fracture and Structural Integrity, 2024)
The use of Areca sheath in developing a newer composite material is proposed in this article. The Areca sheath particulates are extracted by pulverizing long sheaths into different sizes of particulates and are reinforced into the epoxy to process the composites. The study evaluated these composites' macroscopic and vibrational properties, revealing that those with coarse particulates demonstrated superior tensile and flexural strengths, impact strength, hardness, and natural frequency. Notably, the coarse epoxy composite with a 10% weight fraction of particulates exhibited tensile strength and modulus values of 24 MPa and 1050 MPa, respectively. These findings suggest that incorporating a 10% weight fraction of coarse Areca sheath particulates into epoxy resin significantly enhances the composite's macroscopic and vibrational properties, making it a promising material for various building applications like Partition panels, Ceiling Panels, and similar applications.
Keywords: Natural fibres; free Vibration; Natural frequency; Mechanical Properties; Damping factor; Epoxy Composites